Kajian Kitab Hadis (Telaah Kitab Hadis al-Nihayah fi al-Fitan wa al-Malahim) - Muhyidin Azmi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
This article attempts to examine the book of al-Nihayah fi al-Fitan wa al-Malahim which is a book of hadith written by Ibn Kathir. Kitab al-Nihayah fi al-Fitan wa al-Malahim is the second part of the book of al-Bidayah. Kitab al-Nihayah fi al-Fitan wa al-Malahim contains about the signs of doomsday, major events that have and will occur before the coming of doomsday, a picture of heaven and hell excess of the book al-Nihayah fi al-Fitan wa al-Malahim is an explanation of ma'sni al-hadith, the quality of the hadith, and some rijal al-hadith. While the shortcomings of the book al-Nihayah fi al-Fitan wa al-Malahim is that not all the traditions written in it are complete, and the composition is not systematic. The traditions collected in the book of al-Nihayah fi al-Fitan wa al-Malahim are included in the difficult category.